@@ -18,12 +18,12 @@ Alternate strategy for Y1, Y2

or, expanded into the form we've been working with:

-               let u =    Y (\u g x. (\f. A) (u g))  in
-               let g =    Y (  \g y. (\f. B) (u g))  in
+               let u =    Y (\u g. (\f x. A) (u g))  in
+               let g =    Y (  \g. (\f y. B) (u g))  in
let f =                        u g    in
C

-       We abstract the Y1 and Y2 combinators from this as follows:
+       We could abstract Y1 and Y2 combinators from this as follows:

let Yu = \ff.    Y (\u g. ff ( u      g        ) g)  in
let Y2 = \ff gg. Y (  \g. gg (Yu ff   g        ) g)  in
@@ -35,9 +35,9 @@ Alternate strategy for Y1, Y2

*      Here's the same strategy extended to three mutually-recursive functions. `f`, `g` and `h`:

-               let v = Y (\v g h x.      (\f. A) (v g h)) in
-               let w = Y (  \w h x. (\g. (\f. B) (v g h)) (w h)) in
-               let h = Y (    \h x. (\g. (\f. C) (v g h)) (w h)) in
+               let v = Y (\v g h.      (\f x. A) (v g h)) in
+               let w = Y (  \w h. (\g. (\f y. B) (v g h)) (w h)) in
+               let h = Y (    \h. (\g. (\f z. C) (v g h)) (w h)) in
let g =                                     w h in
let f =                            v g h in
D